Dampak Penggunaan Teknologi Blockchain terhadap Transparansi dan Akuntabilitas dalam Manajemen Rantai Pasok - Lina Marlina (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
Supply chain management is a crucial aspect in improving the efficiency and competitiveness of companies. Blockchain technology has emerged as an innovative solution to improve transparency and accountability in supply chain management. This study aims to examine the impact of blockchain technology implementation on transparency and accountability in supply chain management of manufacturing companies in Indonesia. The research method uses a case study approach with data collection through in-depth interviews, observations, and document analysis in three manufacturing companies that have adopted blockchain technology. The results of the study show that blockchain improves transaction transparency and real-time product tracking, reduces the risk of fraud and recording errors, and accelerates the internal audit process. In addition, this technology also supports increased accountability between stakeholders by providing data that cannot be manipulated. However, implementation challenges include high initial costs and the need for competent human resources. This study recommends special training and collaboration between companies to optimize the benefits of blockchain technology in the supply chain. These findings contribute to the development of more transparent and accountable supply chain management in the digital era.